La Secretaría Nacional de la Mujer y la Sección Femenina. Ecos hispanistas en la dictadura militar chilena (1973-1990) - Tessada, Vanessa (CUADERNOS KÓRE, 2011)
This article explores the connections between the Franco's dictatorship, in Spain, and Pinochet's dictatorship, in Chile, through the analysis of two institutions: the Female Section and the National Women's Secretariat. We assume that the "Hispanismo" was a cultural, ideological and material base that joined the both regimes. This ideology contributed to the delineation of a gender discourse. Thus, what would allow us to measure the relationship between both institutions and consider the similarities and ideological differences among the two regimes, is the analysis of the discourse raised by the Female Section and its institutional organization, as well as the gender discourse of the Pinochet's government and the functioning of the National Women's Secretariat.
Keywords: hispanism; gender; dictatorship; Chile; Spain; XX century history